Nonequivalence of membrane voltage and ion-gradient as driving forces for the bacterial flagellar motor at low load. - Lo, C; Leake, M; Pilizota, T; Berry, R (2007)
Many bacterial species swim using flagella. The flagellar motor couples ion flow across the cytoplasmic membrane to rotation. Ion flow is driven by both a membrane potential (V(m)) and a transmembrane concentration gradient. To investigate their relation to bacterial flagellar motor function we developed a fluorescence technique to measure V(m) in single cells, using the dye tetramethyl rhodamine methyl ester. We used a convolution model to determine the relationship between fluorescence intensity in images of cells and intracellular dye concentration, and calculated V(m) using the ratio of intracellular/extracellular dye concentration. We found V(m) = -140 +/- 14 mV in Escherichia coli at external pH 7.0 (pH(ex)), decreasing to -85 +/- 10 mV at pH(ex) 5.0. We also estimated the sodium-motive force (SMF) by combining single-cell measurements of V(m) and intracellular sodium concentration. We were able to vary the SMF between -187 +/- 15 mV and -53 +/- 15 mV by varying pH(ex) in the range 7.0-5.0 and extracellular sodium concentration in the range 1-85 mM. Rotation rates for 0.35-microm- and 1-microm-diameter beads attached to Na(+)-driven chimeric flagellar motors varied linearly with V(m). For the larger beads, the two components of the SMF were equivalent, whereas for smaller beads at a given SMF, the speed increased with sodium gradient and external sodium concentration.